Estudio de la fenología de la planta de café (Coffea arabica L.) para el buen manejo de la finca - Madriz Salinas, J. del C.; Pavon Sabogal, G.A.; Blanco Navarro, M.A. Asesor; Haggar, J. Asesor; Moraga Quezada, P. Asesor (Managua (Nicaragua), 2001)
Sumario (Es)
Ilus.; 28 ref.
Tesis (Ing Agr)
Keywords: COFFEA ARABICA; FENOLOGIA; MANEJO DE FINCAS; NICARAGUA